PENGARUH PENAMBAHAN TEPUNG GAPLEK DENGAN TINGKAT BERBEDA TERHADAP KANDUNGAN NUTRISI SILASE LIMBAH SAYURAN - Tri Atika; Liman ,; Rudy Sutrisna (JURNAL ILMIAH PETERNAKAN TERPADU, 2015)
The purpose of this research was determined to: 1) the effect of additioning cassava flour with different level against to the nutrition qualities (fat, fiber, protein, and NFE) of vegetable waste silage; 2) the best additioning of cassava flour against to the nutrition qualities (fat, fiber, protein, and NFE) of vegetable waste silage. This research used Completely Randomized Design (CRD) with five treatments by adding cassava flour as accelerator (0%, 5%, 10%, 15%, and 20%) and with three repetition. Data were analyzed with Analysis of Varians and continued with Least Significant Difference Test (LSD) 0,05. The result of this research showed that waste vegetable silage with different level adding of cassava flour was significant (P<0,05) to the nutrition qualities (fat, fiber, protein, and NFE) of vegetable waste silage. The best treatment for protein contents of vegetable waste silage was addition by 0% cassava flour, 20% for fat and NEF, and 15% for fiber. Keywords: (Silage, Dried Cassava Flour, Waste Vegetable, Nutrition Content)